Succeeding CORONA: declassified HEXAGON intelligence imagery for archaeological and historical research. (June 2022) - Hammer, Emily; FitzPatrick, Mackinley; Ur, Jason
Abstract: Abstract : Over the past 25 years, CORONA satellite imagery has become an integral part of archaeological research, especially for arid, sparsely vegetated regions such as the Middle East. Since 2020, a new archive of satellite imagery gathered by the US spy satellite programme that succeeded CORONA—HEXAGON—has become widely available for download via the United States Geological Survey. This photographic archive has enormous potential for archaeological research. Here, the authors seek to lower the barriers to accessing and using this imagery by detailing the background, technical specifications and history of the HEXAGON archive. Four case studies illustrate the benefits and limitations of HEXAGON imagery for archaeological and historical research in the Middle East and beyond.